CANCELLATION OF MARRIAGE AND ITS LEGAL CONSEQUENCES IN THE LEGAL SYSTEM IN INDONESIA - Karina, Ica; Banjarnahor, Jupri Wandy (ANAYASA : Journal of Legal Studies, 2023)
The aim of this research is to determine the legal regulations regarding marriage annulment in Indonesia and the legal consequences of marriage annulment. This type of research is normative research, namely a legal research method carried out by examining library materials with the data used being secondary data. Data collection was carried out by studying legal regulations regarding marriage annulment, by identifying regulations regulated in law regarding the causes of marriage annulment, as well as conducting a literature search relating to statutory regulations and problems.  The results of the research show that the regulation of marriage annulment in Indonesia is regulated in the Marriage Law, which states that a marriage can be annulled if the parties do not fulfill the requirements for carrying out the marriage. The conditions referred to are material requirements and formal marriage requirements. The material conditions of marriage are conditions that are inherent in the parties who will enter into marriage. Formal requirements for marriage regulate the procedures for marriage.The legal consequence of an annulment of marriage, namely for husband and wife, is the termination of the relationship between husband and wife. With respect to children, the decision to annul a marriage does not apply retroactively as stated in Article 28 paragraph 2 point a of the Marriage Law. Children born from annulled marriages remain as legitimate children. In this way, the child remains the responsibility of both parties. For joint assets in a marriage that has been annulled, the division of joint assets is in accordance with the division of joint assets due to divorce as regulated in Article 37 of the Joint Property Law.